Study of runaway electron dynamics at the ASDEX Upgrade tokamak during impurity injection using fast hard x-ray spectrometry. (30th September 2021) - Shevelev, A.; Khilkevitch, E.; Iliasova, M.; Nocente, M.; Pautasso, G.; Papp, G.; Molin, A.D.; Pandya, S.P.; Plyusnin, V.; Giacomelli, L.; Gorini, G.; Panontin, E.; et al.
Abstract: To study the runaway electron (RE) dynamics during plasma discharge and develop scenarios for disruption mitigation, a hard x-ray (HXR) spectrometric system has been developed and commissioned at the ASDEX Upgrade tokamak (AUG). The diagnostic system consists of two high-performance spectrometers based on LaBr3(Ce) scintillation detectors supplied with advanced electronics and analysis algorithms. These spectrometers view the AUG tokamak chamber quasi-radially at the equatorial plane. The measurements were carried out in the RE beam generation regimes by injecting argon into a deuterium plasma. In the interaction of a developed RE beam with a heavy gas target, powerful bremsstrahlung flux is induced, reaching energy close to 20 MeV. The electron energy distributions were reconstructed from the measured HXR spectra by deconvolution methods. The experimentally obtained maximum RE energies at different discharge stages were compared with relativistic test particle simulations that include the effect of toroidal electric field, plasma collisional drag force, synchrotron deceleration force. It was observed that the electrons attain their maximum energies within 50–100 ms after the gas injection. It gradually decreases due to the drop in loop voltage, energy loss due to synchrotron radiation emission and collisions dissipation of energy with the background plasma. HXR measurements at the discharge with multiple deuterium pellet injections allowed observing the effects of plasma cooling and argon ion recombination after the pellet injections. Argon density in AUG plasma after massive gas injection was estimated using HXR measurements.